Peningkatan Kemampuan Menulis Karangan Deskripsi Siswa Melalui Model Pembelajaran COR2SF dengan Berbantuan Media Audio Visual - Jusnidar Jusnidar; Andi Muhammad Irfan Taufan Asfar; Andi Muhammad Iqbal Akbar; Andi Fitriani; Andi Megawati (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2021)
The research objective was to determine the improvement of students' writing ability in writing descriptions by using the COR2SF learning model assisted by audio-visual media. Quantitative method, this research uses quasi-experimental research design (quasi experiment), using a control group design, in this design two groups are selected not random. The population of SMP Negeri 1 Kahu used purposive sampling sample, namely the control class class VIII A and the experimental class class VIII B. The experimental class was given treatment using the COR2SF learning model while the control class was not given a modified COR2SF learning model. The techniques used in collecting data in this study were observation, interviews, questionnaires, tests, documentation. The results of observations that have been made at SMP Negeri 1 Kahu, found problems in class VIII C after carrying out apprenticeship 2.The first problem was found in the teaching and learning process in class VIII C, namely students were less active in the learning process, tended to play around during the process learning. This problem is seen when the teacher teaches, only about 50% of active students are really serious and able to do the assignments given by the teacher. Of the 31 students, only 15 of them were able to get scores that really reached the KKM while the other 16 had the scores that had not reached the KKM number, for other class VIII C students were only able to do low-level questions.